Sikap Pandang Bangsa Melayu terhadap Binatang Berdasarkan Peribahasa dalam Bahasa Melayu - Icuk Prayogi (Kibas Cenderawasih : Jurnal Ilmiah Kebahasaan dan Kesastraan, 2019)
Binatang tahan palu, manusia tahan kias: It is no need to teach people through violence as it can be done through the use of satire or metaphor. Proverb is considered as local wisdom. The satire using animal metaphor is considered as a force in identifying local knowledge on the behaviors of animals and also the attitudes of the local society towards the animal to satirize the society members who deviate from the customary conventions. That is, there are demands from the society as a whole so that the deviant members of society can be improved through satire, primarily using the concepts taken from animals around. Taking the concept of animals around can then be regarded as a representation of the attitude or perception of society as a whole to the animals around them. Thus, it can be said that animals have an important role in the people’s culture of a nation. This paper will review the metaphors in proverbs using the concept of animals in order to know people’s perception of the animals around.